High-Fidelity Analysis of Perioperative QTc Prolongation. (February 2016) - Duma, Andreas; Pal, Swatilika; Helsten, Daniel; Stein, Phyllis K.; Miller, J. Philip; Nagele, Peter
Abstract : BACKGROUND: Prolongation of the QTc interval indicates abnormal cardiac repolarization. A recent study has shown that postoperative QTc prolongation is common. However, it is unknown whether QTc prolongation is an isolated postoperative phenomenon or occurs regularly during surgery, or whether the type of anesthesia influences its incidence. METHODS: To answer this question, we conducted a prospective cohort study ( n = 300), where QTc duration was continuously recorded by 12-lead Holter electrocardiogram from 30 minutes preoperatively to up to 60 minutes postoperatively. QTc prolongation was compared between adult patients with at least 1 cardiac risk factor undergoing general ( n = 101) or spinal anesthesia ( n = 99) for orthopedic surgery, or local anesthesia ( n = 100). Primary outcome was intraoperative QTc increase (ΔQTc, as defined by the intraoperative-to-preoperative QTc duration difference). The incidence of long QTc episodes (QTc > 500 milliseconds for at least 15 minutes) was also determined. RESULTS: Significant QTc prolongation (median; interquartile range [IQR]) occurred during general anesthesia (ΔQTc, +33 milliseconds; IQR, +22 to 46 milliseconds) and spinal anesthesia (ΔQTc, +22 milliseconds; IQR, +12 to 29 milliseconds), whereas no QTc prolongation was observed during local anesthesia (biopsy, n = 53: ΔQTc, +4 milliseconds; IQR, −4 to +7 milliseconds; coronary angiography, n = 47: ΔQTc, +6 milliseconds; IQR, −5 to +16 milliseconds). The incidence of long QTc episodes was significantly different between general anesthesia ( n = 6/63, 9.5%), spinal anesthesia ( n = 1/56, 1.8%), local anesthesia for biopsy ( n = 0/46, 0%), and coronary angiography ( n = 0/19, 0%; P = 0.045). CONCLUSIONS: These results indicate that QTc prolongation is not an isolated postoperative phenomenon and is common during surgery under general and spinal anesthesia. Abstract : Supplemental Digital Content is available in the text.Published ahead of print October 26, 2015